2013
DOI: 10.1111/dsu.12065
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Multicenter Clinical Trial of a Minimally Invasive Temperature-Controlled Bipolar Fractional Radiofrequency System for Rhytid and Laxity Treatment

Abstract: Real-time temperature-controlled FRF is a highly reproducible, safe, effective nonsurgical treatment of face and neck rhytides and laxity and provides important insights into neocollagenesis, neoelastogenesis, and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 19 publications
2
36
0
1
Order By: Relevance
“…Six months after a single microneedle fractionated bipolar RF treatment, patients were noted to have a 25.6% mean improvement in facial rhytides and a 24.1% improvement in facial and neck laxity. 109 Other studies have substantiated significant improvements in skin laxity and rhytides at 6 months following a single treatment with such a device. 99,110 The noninsulated microneedle devices have advantages over the earlier, fully insulated microneedles.…”
Section: Fractional Radiofrequencymentioning
confidence: 97%
“…Six months after a single microneedle fractionated bipolar RF treatment, patients were noted to have a 25.6% mean improvement in facial rhytides and a 24.1% improvement in facial and neck laxity. 109 Other studies have substantiated significant improvements in skin laxity and rhytides at 6 months following a single treatment with such a device. 99,110 The noninsulated microneedle devices have advantages over the earlier, fully insulated microneedles.…”
Section: Fractional Radiofrequencymentioning
confidence: 97%
“…The treatment area extended from the nasolabial and melolabial folds medially, preauricular region laterally, and inferior margins of the submental and submandibular regions inferiorly, as previously described. 1 All subjects received a single pass treatment. After each pulse, the FRF applicator was withdrawn, repositioned, and activated on the next treatment area until the target zone was fully treated.…”
Section: Fractional Radiofrequency Treatmentmentioning
confidence: 99%
“…1 Before and after photographs of subjects treated with 1 FRF session were sent to blinded board-certified physicians for grading using the Fitzpatrick scale for rhytides 2 and Alexiades scale for laxity. 3 The study showed that the subcohort with >20% improvement from baseline scores were treated using temperature and pulse duration settings that were lower than the subcohort with <20% improvement (66.7°C, 4.2 seconds vs 69.5°C, 4.9 seconds, respectively).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown with real-time temperature feedback experiments that denaturation temperature of collagen ranges between 65 and 70 °C but is also dependent on the time of laser light exposure; in general, for every 5 °C decrease in temperature, a tenfold increase in time is needed to achieve the same degree of denaturation (Alexiades-Armenakas et al 2013 ). However, once collagen fi bers have been denatured by laser-generated heat, collagen rapidly contracts as fi bers shrink to one-third of their length resulting in immediate skin tightening.…”
Section: Mechanism Of Light: Tissue Effectmentioning
confidence: 99%